UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KARAKTER RELIGIUS SISWA KELAS VII DI SEKOLAH MENENGAH PERTAMA NEGERI 1 GALING TAHUN PELAJARAN 2022-2023 - Raji’in; Susilawati, Mauizatul Hasanah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The aim of this research is to reveal: 1) Forms of Islamic Religious Education Teachers' Efforts in Developing the Religious Character of Class VII Students at SMP N 1 Galing District for the 2022-2023 Academic Year. 2) PAI Teachers' Efforts to Develop Religious Character in Class VII Students at SMP N 1 Galing District for the 2022-2023 Academic Year. 3) Supporting and Inhibiting Factors for PAI Teachers' Efforts in Developing the Religious Character of Class VII Students at SMP N 1 Galing District for the 2022-2023 Academic Year. This research uses a qualitative approach and descriptive research type. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data collection, data display, and conclusions. The results of the research show that: 1) The forms of Islamic religious education teachers' efforts are by teaching, providing guidance, coaching, providing role models and advice, familiarizing and disciplining students to behave in accordance with the teachings of the Islamic religion, praying before and after the learning process and creating an environment that religious. 2) The PAI teacher's efforts in developing religious character in class VII at SMP Negeri 1 Galing, namely the teacher provides an example by entering class on time, instilling good behavior that can be captured and used as a habit by students, getting used to praying before and after learning, creating conducive atmosphere by shaking hands with the teachers, internalization and integration of the vision and mission into what is in accordance with the development of religious character. 3) Supporting and inhibiting factors for the efforts of Islamic Religious Education teachers in developing religious character in class VII students at SMP Negeri 1 Galing are as follows : Supporting factors are pre-school experience, level of intelligence, learning motivation, attitudes and study habits. Inhibiting factors are internal factors and external factors.